A transterritorialidade como mecanismo de responsabilização de empresas por violações aos Direitos Humanos - Atchabahian, Ana Cláudia Ruy Cardia (2018)
The present PhD thesis aims at establishing the foundations of a new mechanism for corporations’ judicial accountability for human rights violations: the transterritoriality. Based on multidisciplinary literature, deriving from Sociology, International Relations, International Law, International Law of Human Rights, Sociology of Law and from International Constitutional Law, a mechanism shall be built – that may result in theory – with the objective of confirming the applicability of the rules of Private International Law, Public International Law and International Human Rights Law by the States and the national judges in a heterarchical and transversal manner, resulting in a true dialogue between the national jurisdictions and International Courts in the punishment of corporations which violate human rights. Such model presents itself as an alternative to the discussions of a treaty on the subject, especially if one considers the difficulty of attaining consensus between States regarding the negotiated provisions, in addition to the rigidity typical to the International Law structure, which still prioritizes States as the main subjects of its discipline. With connection to the research methods employed, the qualitative and deductive methods shall be utilized, based on interdisciplinary research. For the development and the conclusion of the critical analysis about the proposed theme, as well as the preparation of the thesis herein defended, current primary and secondary sources with respect to the Business and Human Rights theme shall be investigated